The privacy fallacy : harm and power in the information economy / Ignacio Cofone. - Cofone, Ignacio N., 1987- (Cambridge University Press, 2024)
Our privacy is besieged by tech companies. Companies can do this because our laws are built on outdated ideas that trap lawmakers, regulators, and courts into wrong assumptions about privacy, resulting in ineffective legal remedies to one of the most pressing concerns of our generation. Drawing on behavioral science, sociology, and economics, Ignacio Cofone challenges existing laws and reform proposals and dispels enduring misconceptions about data-driven interactions. This exploration offers readers a holistic view of why current laws and regulations fail to protect us against corporate digital harms, particularly those created by AI. Cofone then proposes a better response: meaningful accountability for the consequences of corporate data practices, which ultimately entails creating a new type of liability that recognizes the value of privacy.